2020
DOI: 10.21203/rs.3.rs-35112/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA LINC00342 contributes to the growth and metastasis of colorectal cancer via targeting miR-19a-3p/NPEPL1

Abstract: Background Long intergenic non-protein coding RNA 00342 (LINC00342) has been identified as a novel oncogene. However, the functional role of LINC00342 in colorectal cancer (CRC) remains unclear. Methods The expression of LINC00342 is detected by real-time PCR (RT-PCR) analysis. Cell proliferation, migration and invasion and xenograft model are examined to analyze the biological functions of LINC00342 in vitro and in vivo using colony formation, would healing and transwell analyses. Dual-luciferase reporter and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…it is well-known that abnormal and uncontrolled proliferation is a characteristic of cancer cells (19). Furthermore, invasion and migration are considered as two dominant processes for tumor metastasis, which leads to cancer-associated mortality (20). in this regard, interruption of the aforementioned processes is an effective method for resistance of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…it is well-known that abnormal and uncontrolled proliferation is a characteristic of cancer cells (19). Furthermore, invasion and migration are considered as two dominant processes for tumor metastasis, which leads to cancer-associated mortality (20). in this regard, interruption of the aforementioned processes is an effective method for resistance of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on univariate and multivariate Cox regression analyses, we ultimately obtained 7 m6A-related lncRNAs that were signi cantly correlated with prognosis (LINC00342, AC018752.1, RPL34-AS1, AF117829.1, AC009948.2, SNHG10, and AL133243.3) and constructed a prognosis risk model. Studies have found that long intergenic non-protein coding RNA 00342 (LINC00342) can regulate the growth, invasion and metastasis of colorectal cancer and NSCLC cells and is closely associated with the poor prognosis of patients [48][49]. The lncRNA ribosomal protein L34 antisense RNA 1 (RPL34-AS1) is localized on human chromosome 4q25 and has antitumor effects in esophageal carcinoma and papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies used CRC cell lines SW480 and SW620, but their conclusions contradicted each other. Moreover, miR-203a-3p has been revealed as a tumor suppressor in gastric cancer [22], nasopharyngeal carcinoma [23] and non-small-cell lung cancer [24]. It is hard to say which study is more reliable.…”
Section: Discussionmentioning
confidence: 99%